1998
DOI: 10.1111/j.1749-6632.1998.tb11188.x
|View full text |Cite
|
Sign up to set email alerts
|

The PACAP Ligand/Receptor System Regulates Cerebral Cortical Neurogenesisa

Abstract: The PACAP ligand/type I receptor system is expressed throughout the embryonic nervous system, suggesting roles in regulating neural patterning and neurogenesis. In the forebrain, precursors of the six-layered cerebral cortex cease dividing in a highly reproducible spatiotemporal sequence. The time of cell cycle exit in fact determines neuron laminar fate. Our studies indicate that PACAP signaling may elicit cortical precursor withdrawal from the cell cycle, antagonizing mitogenic stimulators. PACAP inhibited e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 53 publications
0
31
1
1
Order By: Relevance
“…From this point of view, it should be noted that PACAP significantly increases both MTT reduction and neurosphere size. This polypeptide was shown to regulate the proliferation and differentiation in neural progenitor cells during embryonic development (63). In our hands, mRNA expression was not detected for any isoforms of adrenergic β-receptors known to be positively coupled to adenylyl cyclase in undifferentiated neural progenitor cells.…”
Section: A Role Of Group III Mglur In Neurogenesismentioning
confidence: 68%
“…From this point of view, it should be noted that PACAP significantly increases both MTT reduction and neurosphere size. This polypeptide was shown to regulate the proliferation and differentiation in neural progenitor cells during embryonic development (63). In our hands, mRNA expression was not detected for any isoforms of adrenergic β-receptors known to be positively coupled to adenylyl cyclase in undifferentiated neural progenitor cells.…”
Section: A Role Of Group III Mglur In Neurogenesismentioning
confidence: 68%
“…These include widely expressed growth factors [bFGF, EGF, IGF, TGF-␤, and pituitary adenylate cyclase-activating polypeptide (PACAP)], neurotrophic factors (NT3, NT4, BDNF, and NGF), and neurotransmitters (GABA, glutamate, VIP, and monoamines). Factors that have been reported to promote neuroblast proliferation include NGF (Cattaneo and McKay, 1990), bFGF (Ghosh and Greenberg, 1995;Cavanagh et al, 1997), EGF (Burrows et al, 1997), IGF (Nielsen and Gammeltoft, 1990;Ye et al, 1996), and VIP (Gressens et al, 1998), whereas 5-hydroxytryptamine (5-HT) (Lavdas et al, 1997), norepinephrine (Ghiani et al, 1999), glutamate and GABA (LoTurco et al, 1995), and PACAP (Lu and DiCicco-Bloom, 1997;DiCicco-Bloom et al, 1998) have been shown to inhibit proliferation and/or to elicit cell-cycle withdrawal.…”
Section: Candidate Molecule For the Mitogenic Effectmentioning
confidence: 99%
“…Glutamate and GABA influence DNA synthesis of cortical precursors in the rat ventricular and subventricular zones (LoTurco et al, 1995, Haydar et al, 2000. There is evidence suggesting that the cortical plate exerts an inhibitory feedback influence on proliferation in the ventricular zone (DiCicco-Bloom et al, 1998;Polleux et al, 1998) that could be relayed by descending corticofugal axons (Kim et al, 1991;Miller et al, 1993;McConnell et al, 1994;Meyer et al, 1998).…”
Section: Afferent Control Of Morphogenesis In the Cnsmentioning
confidence: 99%
“…It is widely distributed in neurons of the brain and peripheral nervous system [2], and has multiple transmitter and trophic functions [3]. PACAP affects neuronal cell cycle exit during central nervous system formation [4], promotes neuronal differentiation in cultured rat sympathetic neuroblasts [5,6], differentially modulates proliferation of central and peripheral neuroblasts [7], stimulates neuritogenesis in PC12 cells [8,9] and regulates neuron-specific gene expression in human neuroblastoma cell lines [10]. PACAP prevents apoptotic cell death and protects cultured rat cortical neurons against glutamate-induced cytotoxicity [11], and dopaminergic neurons against 6-hydroxydopamine-induced cytotoxicity [12].…”
Section: Introductionmentioning
confidence: 99%